2021
DOI: 10.1002/arcp.1072
|View full text |Cite
|
Sign up to set email alerts
|

Do consumers care about morality? A review and framework for understanding morality's marketplace influence

Abstract: There are many ways consumers' morality has been shown to impact their marketplace behavior. We present a theoretical framework for how to conceive of and study marketplace morality in an attempt to unify these disparate findings. First, we describe two common conceptualizations of marketplace morality: (a) the attributelevel approach (where a product attribute fits within a category that is normatively considered moral) and (b) the person-level approach (where consumers differ in the extent to which they disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 209 publications
(243 reference statements)
0
7
0
Order By: Relevance
“…Past research has examined insensitivity to consequences only among GE food opponents. Because people are more likely to moralize negative attitudes than positive ones, it may be that there are no consequence-insensitive GE supporters (Philipp-Muller et al, 2022). However, in a pilot study (described in more detail in the Supplemental Material), we found that both GE crop supporters and opponents said they based their attitudes on their "gut feelings" to a surprising extent (M = 4.0 for supporters; M = 4.2 for opponents on a 1 [Not at All]-6 [Absolutely] scale).…”
Section: Consequence Insensitivity Among Ge Supportersmentioning
confidence: 99%
“…Past research has examined insensitivity to consequences only among GE food opponents. Because people are more likely to moralize negative attitudes than positive ones, it may be that there are no consequence-insensitive GE supporters (Philipp-Muller et al, 2022). However, in a pilot study (described in more detail in the Supplemental Material), we found that both GE crop supporters and opponents said they based their attitudes on their "gut feelings" to a surprising extent (M = 4.0 for supporters; M = 4.2 for opponents on a 1 [Not at All]-6 [Absolutely] scale).…”
Section: Consequence Insensitivity Among Ge Supportersmentioning
confidence: 99%
“…Consumption behavior is naturally associated with morality, since it raises issues of perceived fairness, as well as self versus social interests (Grayson, 2014; Harrison et al, 2005; Philipp‐Muller et al, 2022; Wilk, 2001). Today, consumers place increasing importance on the morality of companies, which in turn impacts consumer choice (Freestone & McGoldrick, 2008; Grappi et al, 2013; L. Hassan et al, 2013; Hilton, 2009; Nielsen & McGregor, 2013; Smith, 1990).…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
“…Thus, moral violations can lead to poorer brand or company evaluations. Companies' moral actions are particularly liable to influence consumer evaluations and subsequent choices when the values are emotional or are seen as relevant to the values and identity of the consumer (Philipp‐Muller et al, 2022).…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Both positive and negative triple bottom line messages can impact firms’ ethical reputation because they act as a signal that can increase (in the case of positive messages) or decrease (in the case of negative messages) consumer perceived ethicality (Brunk and de Boer, 2020). Although the issue of ethicality is inherent to triple bottom line conceptualization, it is rarely empirically addressed from a consumer perspective (Philipp-Muller et al , 2022). More specifically, the influence of triple bottom line messages on consumer perceived ethicality of the brand, spillover effects on consumer perceptions of brand and product attributes and even the effects of each triple bottom line dimension on consumer perceptions and purchase intentions need broader exploration (Chen and Huang, 2018).…”
Section: Introductionmentioning
confidence: 99%